DESIGNING AND EFFICIENCY EFFECT OF AUTOMATIC BALL-CLEANING SYSTEM FOR CONDENSER 180-KTsS-1 OF TURBINE Т-180/210-130-1 LMZ. Part 1 - Yu. A. Zenovich-Leshkevich-Ol’pinskiy; A. Yu. Naumov; A. Yu. Zenovich-Leshkevich-Ol’pinskaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
In order to reduce losses in the cooling source (condenser) and to increase effectiveness of fuel-and-power resources utilization, the authors present a modern automatic ball-cleaning system for the pipes of condenser 180-KTsS-1 of turbine unit Т-180/210-130-1 LMZ of Gomel CHP-2. The article examines exploitation challenges of the steam turbine condensers and methods of clearing them from sedimentations. Depending on the sedimentation character and composition, and the quality of cooling water at the power plant, they apply various methods of the condenser tubes clearing: heat drying, vacuum dehydration, acid-washing, pipes-shooting with water and water-air pistols, ablution with high-pressure water jet etc. All the applied cleaning methods are the periodical means to fight the sedimentations and require the turbine halting or unloading, predetermine the equipment operating between clearings with constantly smearing cooling surfaces of the condensers, i.e. with reduced efficiency of equipment operation.The installation of the ball-cleaning system practically excludes defects of the chemical and mechanical cleaning methods, which leads to the condenser pipes life-in-service increase, the full-flow condensate quality improvement, reliability and efficient performance enhancement of the steam turbines equipment. The authors consider developed algorithms of data processing and designed system control of the condenser cleaning that allowed realizing its operation in automatic mode.